3D printed superparamagnetic stimuli-responsive starfish-shaped hydrogels. Issue 4 (April 2023) - Mohammed, Ali A.; Miao, Jingqi; Ragaisyte, Ieva; Porter, Alexandra E.; Myant, Connor W.; Pinna, Alessandra
Abstract: Magnetic-stimuli responsive hydrogels are quickly becoming a promising class of materials across numerous fields, including biomedical devices, soft robotic actuators, and wearable electronics. Hydrogels are commonly fabricated by conventional methods that limit the potential for complex architectures normally required for rapidly changing custom configurations. Rapid prototyping using 3D printing provides a solution for this. Previous work has shown successful extrusion 3D printing of magnetic hydrogels; however, extrusion-based printing is limited by nozzle resolution and ink viscosity. VAT photopolymerization offers a higher control over resolution and build-architecture. Liquid photo-resins with magnetic nanocomposites normally suffer from nanoparticle agglomeration due to local magnetic fields. In this work, we develop an optimised method for homogenously infusing up to 2 wt % superparamagnetic iron oxide nanoparticles (SPIONs) with a 10 nm diameter into a photo-resin composed of water, acrylamide and PEGDA, with improved nanoparticle homogeneity and reduced agglomeration during printing. The 3D printed starfish hydrogels exhibited high mechanical stability and robust mechanical properties with a maximum Youngs modulus of 1.8 MPa and limited shape deformation of 10% when swollen. Each individual arm of the starfish could be magnetically actuated when a remote magnetic field is applied. The starfish could grab onto a magnet with all arms when a central magnetic field was applied. Ultimately, these hydrogels retained their shape post-printing and returned to their original formation once the magnetic field had been removed. These hydrogels can be used across a wide range of applications, including soft robotics and magnetically stimulated actuators. Graphical abstract: Image 1